PYOCIN S5 ACTIVITY AGAINST PSEUDOMONAS SYRINGAE PHYTOPATHOGENIC STRAINS - Balko, Oleksandr; Zelena, Lyubov; Balko, Olha; Avdeeva, Liliya (Journal of microbiology, biotechnology and food sciences, 2024)
Pseudomonas syringae is the most frequently isolated bacterial plant pathogens. Previously we revealed a number of Pseudomonas aeruginosa strains – producers of bacteriocins (pyocins) with high activity against P. syringae. However, it was unknown, which type of pyocins possesses the activity against P. syringae strains. S5 and S1 pyocin genes were observed in the genome of most active strain–producer P. aeruginosa UCM В-333. Pyocins were induced by nalidixic acid (100 μg/ml). Using DEAE-cellulose chromatography we isolated two bacteriocin groups from initial lysate. Substances from the 10th fraction had nuclease activity (pyocin S1) and the 27th fraction - pore-forming activity (pyocin S5). It was revealed that S1 pyocin didn’t lead to growth inhibition of studied bacterial plant pathogens. However pyocin S5 caused appearance of growth inhibition area with diameter 14-20 mm. So, pyocins of S1 and S5 types are active substances in P. aeruginosa UCM В-333 lysates, but only S5 pyocin possess activity against P. syringae strains. fpt A receptor gene was revealed in genomes of all analyzed cultures, including used phytopathogenic strains. This fact can explain wide spectrum of pyocin S5 activity. It is suggested that pyocin S5 can be a potential biocontrol agent against phytopathogenic P. syringae strains.